2021
DOI: 10.1017/s0016756821000315
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional stromatolites from Maastrichtian–Danian Yacoraite Formation, Argentina: modelling and assessing hydrodynamic controls on growth patterns

Abstract: Stromatolites are biogenic sedimentary structures formed by the interplay of biological (microbial composition) and environmental factors (local hydrodynamic conditions, clastic input and/or water chemistry). Well-preserved, three-dimensional (3D) fossil stromatolites are key to assessing the environmental factors controlling their growth and resulting morphology in space and time. Here, we report the detailed analysis of well-exposed, highly informative stromatolite build-ups from a single stratigraphic horiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 73 publications
(109 reference statements)
1
7
0
Order By: Relevance
“…In the lower part of the same section, Frías-Saba et al (2021) described a new microbialitic level composed of domical shapes up to 25 cm. The internal morphology of these domes shows a basal sector with columnar structures alternating with laminated structures and an upper sector with well-developed columns separated by the third-order channels, similar to those described by Villafañe et al (2021). The authors suggested that these microbialites developed in a subtidal/intertidal environment with moderate to high hydrodynamic energy were controlled by a shallowing upward process.…”
Section: Microbialites In Tres Cruces Sub-basinsupporting
confidence: 66%
See 3 more Smart Citations
“…In the lower part of the same section, Frías-Saba et al (2021) described a new microbialitic level composed of domical shapes up to 25 cm. The internal morphology of these domes shows a basal sector with columnar structures alternating with laminated structures and an upper sector with well-developed columns separated by the third-order channels, similar to those described by Villafañe et al (2021). The authors suggested that these microbialites developed in a subtidal/intertidal environment with moderate to high hydrodynamic energy were controlled by a shallowing upward process.…”
Section: Microbialites In Tres Cruces Sub-basinsupporting
confidence: 66%
“…Later, Cónsole-Gonella et al (2017) presented a complete paleoenvironmental reconstruction, showing the ichnofacies implications describing the presence of five stromatolitic facies, some of them showing a remarkable degree of preservation. On the contrary, Villafañe et al (2021) studied this series and determined the relationship between hydrodynamic energy and these organo-sedimentary structures, defining seven stromatolitic beds in this locality. Finally, at the same locality, Frías-Saba et al (2021) described the influence of bacterial communities, sediment input, and CO 3 saturation of waters on the development of stromatolite microfabrics from Yacoraite Formation (for a detailed stratigraphic column with the position of microbialites, see Villafañe et al 2021).…”
Section: Regional Distribution Of Microbialitic Depositsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of drones would be replaced by tools such as acoustic sonar, something already used in modern environments such as Pavilion Lake (e.g., Mullins and Bird, 2007;Trembanis and Gutsche, 2019). This type of methodology could also be combined with techniques applied for the three-dimensional reconstruction of fossil microbialitic sites such as traditional photogrammetry (Villafañe et al, 2021b), Ground Penetrating Radar (de Lima et al, 2018, among others.…”
Section: The Scope Of This Methodologymentioning
confidence: 99%